2015
DOI: 10.1095/biolreprod.114.121376
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibroblast Growth Factor-18 in Follicular Atresia in Cattle1

Abstract: Although the various members of the fibroblast growth factor (FGF) family are generally mitotic, one member, FGF18, has been shown to increase the rate of apoptosis of ovarian granulosa cells. In the present study, we first determined whether granulosa cells express FGF18 and we then explored the mechanism through which FGF18 increases apoptosis in vitro. Under culture conditions that favored estradiol secretion and CYP19A1 expression, granulosa FGF18 mRNA levels were barely detectable; however, withdrawing go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…E 2 is a major determinant of follicle development and decreases granulosa cell apoptosis in rodents in vivo (Billig et al 1993). Studies with bovine granulosa cells have demonstrated that E 2 can overcome the apoptotic effect of ligands such as FASLG and FGF18 (Quirk et al 2006, Portela et al 2015. Of the main RSR pathways, MAPK3/1 is known to alter CYP19A1 mRNA levels; inhibition of MAPK3/1 phosphorylation increased CYP19A1 mRNA levels in bovine and rodent granulosa cells (Moore et al 2001, Silva et al 2006 and reduced the ability of tumor necrosis factor alpha to increase apoptosis (Morales et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…E 2 is a major determinant of follicle development and decreases granulosa cell apoptosis in rodents in vivo (Billig et al 1993). Studies with bovine granulosa cells have demonstrated that E 2 can overcome the apoptotic effect of ligands such as FASLG and FGF18 (Quirk et al 2006, Portela et al 2015. Of the main RSR pathways, MAPK3/1 is known to alter CYP19A1 mRNA levels; inhibition of MAPK3/1 phosphorylation increased CYP19A1 mRNA levels in bovine and rodent granulosa cells (Moore et al 2001, Silva et al 2006 and reduced the ability of tumor necrosis factor alpha to increase apoptosis (Morales et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the known actions of other FGFs in the ovary, however, FGF18 appears to be a proapoptotic factor. Abundance of FGF18 mRNA and protein is higher in atretic compared with growing bovine follicles, and addition of FGF18 increased the amount of DNA laddering and caspase-3 activation in granulosa cells in vitro (Portela et al 2010(Portela et al , 2015. The mechanisms of action of FGF18 in the follicle have not been fully elucidated, but it may act through a murine double minute 2 (MDM2) and p53 upregulated modulator of apoptosis (PUMA, also known as BBC3) pathway (Portela et al 2015), although it has not yet been shown whether FGF18 alters p53 signaling.…”
Section: The Role Of the Fgf8 Family In Follicle Developmentmentioning
confidence: 99%
“…Abundance of FGF18 mRNA and protein is higher in atretic compared with growing bovine follicles, and addition of FGF18 increased the amount of DNA laddering and caspase-3 activation in granulosa cells in vitro (Portela et al 2010(Portela et al , 2015. The mechanisms of action of FGF18 in the follicle have not been fully elucidated, but it may act through a murine double minute 2 (MDM2) and p53 upregulated modulator of apoptosis (PUMA, also known as BBC3) pathway (Portela et al 2015), although it has not yet been shown whether FGF18 alters p53 signaling. Most intriguingly, FGF18 does not result in the typical phosphorylation of MAPK3/1, but does phosphorylate MAPK14 (also known as p38); increased activity of MAPK14 has been linked to apoptosis in ovarian cells (Uma et al 2003, Bu et al 2006.…”
Section: The Role Of the Fgf8 Family In Follicle Developmentmentioning
confidence: 99%
See 2 more Smart Citations